Estimation of Age in Females of the Red King Crab Paralithodes camtschaticus (Decapoda, Lithodidae) from the Barents Sea Based on Their Size Composition - M.A. Pinchukov (Учёные записки Казанского университета: Серия Естественные науки)
The results from studying the growth and age characteristics of female red king crabs (Paralithodes camtschaticus) in the Barents Sea have been analyzed. Carb specimens were tagged and recaptured in 1993–2002. A total of 39 females with the carapace width over 70 mm were registered. Their growth has been studied by Cleaver's method. According to the data of trawl surveys in 1998–2009, the change of the carapace width during the period between the first and the second captures of tagged females corresponds well to the data on the long-term dynamics in length composition of females. The maximum absolute annual increment in females aged 9 years was 16 mm. This value gradually decreased to 4mm at the age of 15–17 years and increased to 8–9 mm at the age of 18–19 years. The highest relative annual increment of 17% has been observed in females aged 9 years. Subsequently, it gradually decreased to 3–5% as females grew older. The maximum age of females in the Barents Sea has been estimated as 22–23 years. The obtained results allow to reliably identify at first approximation the age of females of P. camtschaticus in the Barents Sea based on their body size. These data can be used for assessing the population growth, as well as for the purposes of biological expertise.